The Impact of Labor Productivity, Producer Confidence, and Exchange Rates on Manufacturing Production Levels in ASEAN-5 Countries from 2015 to 2023 - Merina, Heriska; Nikensari, Sri Indah; Nurjanah, Siti (The Future of Education Journal, 2025)
This study aims to analyze the influence of labor productivity, producer confidence, and exchange rates on manufacturing production levels in the ASEAN-5 countries (Indonesia, Malaysia, Thailand, the Philippines, and Vietnam) during the period 2015–2023. The data used are sourced from the World Bank, the Bank for International Settlements (BIS), Trading Economics, and the statistical agencies of each country, and were analyzed using panel data regression with a Random Effect Model (REM) approach. The results indicate that labor productivity does not significantly affect manufacturing production, producer confidence significantly affects manufacturing production, and the exchange rate significantly affects manufacturing production. The COVID-19 pandemic was not found to significantly reduce production levels due to supply chain disruptions and economic activity restrictions, as production actually increased during the pandemic.